The incidence of chronic viral hepatitis and the analysis of the genetic diversity of hepatitis B and C viruses among the population of Khabarovsk city - Valeriya O. Kotova; Elena A. Bazykina; Lyudmila A. Balakhontseva; Olga E. Trotsenko; Anna V. Kuznetsova (Журнал микробиологии, эпидемиологии и иммунобиологии, 2025)
Introduction. Evaluation of hepatitis virus genotypes diversity plays a significant role in analysis of epidemiological situation in particular territories which allows to trace possible routs of transmission, emergence and spread of new viral variants.